G224(P) Child Abuse Record Keeping and Report Writing Standards (CARRS). (4th June 2013) - Pahuja, A; Burridge, R; Rudran, V
Abstract : Child protection remains a sensitive issue in the UK and is a challenge to Paediatricians and other health care workers. It is well established that a high quality written report is of paramount importance and enables legal teams and juries to form conclusions in the best interests of the child. Unfortunately there are no structured guidelines or training course on how to write a medical report following a child protection medical. Aim: We performed a semi-qualitative assessment of the medical record keeping and the report writing in child physical abuse cases. Method: This was a retrospective notes audit. 50 child protection medicals were audited which had been conducted across the three community paediatric centres for suspected physical abuse physical abuse between September 2010 and August 2011. The medical reports and notes were assessed according to an audit proforma under 4 major headings: Demographic and referral route information, History recording, Consent, Opinion/Plan. These were further subdivided further into 18 points of information based on information requested on the clerking proforma provided for medical personnel. Data were analysed using excel. Data collection quantitative points were assessed by the community specialist registrars and quality of reports and issues of consistency and opinion were assessed by the lead community paediatric consultant with experience and expertise in performing child protection medicals and in preparing medical reports. Results: The results of the audit are summarised in table 1 and figure 1 . Generally quantitative information was collected adequately, although there are some administrative concerns around patient information labels being present on all pages of the proformas used which was not consistently adhered to. On qualitative assessment, in around 85% of cases it was felt that there was a clear and consistent opinion and plan made. Most reports were produced within 48 hours (84%) and copied to relevant professionals (85%). Given some of the loss of information from handwritten proforma to typed report and the wide variation in information provided in the typed reports audited, our Community NHS Trust services have designed a report writing proforma, in an attempt to improve the quality and consistency of information shared with other professionals following a child protection medical examination (Fig. 2: report writing proforma- available if accepted).